Poverty Reduction through Entrepreneurship Programmes - Mohd Jazid, Amirul Iman; Ibrahim, Patmawati; Kartini Rashid, Umi (International Journal of Psychosocial Rehabilitation, 2019)
The issue of poverty has become more serious as the number of aid recipients, according to the statistics provided by Jabatan Kebajikan Masyarakat (JKM) and the State Islamic Religious Council (MAIJ), seems to be increasing. The dependency of recipients on aid shows that the poor are still burdened with poverty problems due to the high standard of living cost and household financial constraints. Under the Human Development Index (HDI), there are three dimensions considered to be able to achieve well-being in life, namely economic/standard of living, education, and health. The ability and productivity of individuals are an important part in assessing a country’s development. Therefore, this study aims to propose entrepreneurship programs to beneficiaries to help them escape poverty and achieve a better standard of living. Methodology: This study has been conducted using the quantitative method. Descriptive tests were performed using SPSS to identify the mean scores, frequency, and percentage obtained for each statement. A total of 260 beneficiaries were identified as respondents representing both poverty agencies, which are JKM and MAIJ. The Friedman test had been done earlier and later found out that economic aspects got the highest ranking. Main findings: The study finds that out of the three dimensions of HDI, namely, economic/standard of living, education, and health, the economic dimension has been proven to have the highest mean rank. This shows that the living economy is a factor that prevents poor people from getting out of poverty. This study also finds that the majority of poor people earn less than RM1,000, and this is one of the main reasons for poor people to be stuck in this state. Therefore, looking at these dimensions, this paper tends to introduce entrepreneurship programs to beneficiaries to help them improve their standard of living. Social implications: The implementation of the entrepreneurial programs for beneficiaries can provide impacts on the local community. Changes through job openings, increased productivity, and different types of product and service production can impact the development of a society. Novelty of the study: Entrepreneurship programs can be enhanced by exposing them to business knowledge through the use of digital technology. The exposure of digital technology in expanding the marketing of products and services can bring the poor to a new level. In addition, assistance to the poor through trainings and courses should also be enhanced by focusing on digital technology concepts.